(3GdchcH GdeJdGdj HTQM bUjOI GdZRGdjs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj , (B1143 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb GdehJ hGdMjGICeG HYOagPG TQM dWja CaQZJg aj bGdH GdJUfja hQUaJgQLG GdGfJcGd Cced JQUja CLd Hg eG GfYbO ef cdeGJ GdbUjOI GdfhfjI hGdLhgQI GdaQjOI GdeVjFI GdefShH (B((3cPG(B) (3Edi GdEeGe CHj MGeO GdZRGdjs
(3BNQgG (B:s
(3hYdjce ef SdGej WjH (B- (3SdGe Gddg Ydjce hKfG (B- (3Cj Ydjce ef SdGej SdGe WjH JWjH Hg fahSce hJbQHg Yjhfce Ke YWa bhdg hKfG, hGdKfGA gh GdeOM Cj Ydjce efj KfGA WjH eHGQc, hbhdg(B: (3Sde Gddg Ydjce LedI eYJQVI Hjf GdeJYGWajf Cj ChUd Gddg Edjce GdSdGe efg SHMGfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 32s
(3eYLe GdeDdajf(B: 2 / 176s
(3EjVGM Gdecfhf(B: 2 / 394s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs